2017
DOI: 10.1038/emm.2017.80
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of miR-223 in the rat liver inhibits proliferation of hepatocytes under simulated microgravity

Abstract: Long-term spaceflight affects numerous organ systems in the body, including metabolic dysfunction. Recently, ample evidence has demonstrated that the liver is a vulnerable organ during spaceflight. However, the changes in hepatocyte proliferation and cell cycle control under microgravity remain largely unexplored. In the present study, we first confirmed that the serum levels of aspartate aminotransferase, alanine aminotransferase and alkaline phosphatase, biochemical markers of liver function, were altered in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 59 publications
1
15
1
Order By: Relevance
“…Furthermore, an inverse correlation of miR-223-3p with an improved cell viability, prevention of cardiomyocyte apoptosis as well as with inhibition of reactive oxygen species and lipid peroxidation was shown in a former study 26 . Similar, elevated levels of miR-223-3p were reported under simulated microgravity in rats with an inhibitory effect on hepatocyte proliferation trough a cyclin dependent kinase 2/Cullin1 (CDK2/CUL1) signaling pathway 11 .…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Furthermore, an inverse correlation of miR-223-3p with an improved cell viability, prevention of cardiomyocyte apoptosis as well as with inhibition of reactive oxygen species and lipid peroxidation was shown in a former study 26 . Similar, elevated levels of miR-223-3p were reported under simulated microgravity in rats with an inhibitory effect on hepatocyte proliferation trough a cyclin dependent kinase 2/Cullin1 (CDK2/CUL1) signaling pathway 11 .…”
Section: Discussionsupporting
confidence: 66%
“…Long term changes commonly affect bones and muscles atrophy. Additionally, an impairment of lung function and liver function as well as a dysregulation of the immune system have been described 8 11 . A decrease in hemoglobin and an increase in glomerular filtration rate (GFR) and levels of myoglobin were reported by our study group 12 .…”
Section: Introductionmentioning
confidence: 99%
“…MiRNAs are endogenous small noncoding RNAs that each can target hundreds of mRNAs (also protein and DNA) and function as post-transcriptional modulators of gene expression, leading to dysregulation of protein expression and/or mRNA levels [ 11 , 27 , 28 ]. Simulated microgravity study detected elevated levels of miR-223 with decreased proliferation of Hepa1-6 cells [ 29 ]. Consistent with this report, our analyses also predicted miR-223 among the top 10 spaceflight-induced miRNAs, which potentially could result in down regulation of several key genes such as ICAM1 , IGF1R and upregulation of TLR4/7 , LPL and CCR3 etc.…”
Section: Resultsmentioning
confidence: 99%
“…Suprisingly the miRNAs that we predict to drive microgravity biological response have been reported to be involved with simulated microgravitry experiments previously reported by other investigators. For example, modeled microgravity-triggered miRNAs have been identified in human peripheral blood lymphocytes (PBL) [ 27 , 50 ], human leukocytes [ 31 ], human lymphoblastoid cells [ 30 ], and in murine hepatoma cell line [ 29 ]. In these studies, miR-223 has been found to regulate cell cycle progression by targeting E2F1, Fbxw7/Cdc4, IGF1R, Cdk2 and TOX and overexpression of the miRNA resulting in suppression of c-Myc expression [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that therapeutic exercise, such as spa exercise, can relieve AS symptoms in adults (13). Suspension also appears to be a promising modality; this method has been regularly applied to mechanical load reduction experiments (14,15). In recent years, tail suspension to the point of no load-bearing has become popular as a microgravity model (16).…”
Section: Tail Suspension Delays Ectopic Ossification In Proteoglycan-induced Ankylosing Spondylitis In Mice Via Mir-103/dkk1mentioning
confidence: 99%